The Effect Of Self–Efficacy Promoting Program on Fear of Fall in Postoperative Total Hip Replacement Older Persons - ใจปิติ หทัยทิพย์; สาสัตย์ ศิริพันธุ์ (Journal of The Royal Thai Army Nurses, 2019)
The quasi experimental research with two group pretest – posttest design aimed to study the effect of self-efficacy promoting program on fear of fall in postoperative total hip replacement older persons. The participants consisted of both male and female older persons admitted in orthopedic ward, Rajavithi hospital. The purpusesive sampling consisted of 44 older persons and random assignment in to control and experiment groups with similar characteristics in terms of age, gender and level of fear of fall. The experimental group underwent a self-efficacy promoting program and control group received conventional care. The self-efficacy promoting program was performed once a week for 4 weeks. The instruments were Self-efficacy promoting program, demographic questionnaire, Mini-Mental State Examination-Thai version 2002, and Fear of fall scale. The reliability of Fall Efficacy Scale, Thai Fall Efficacy Scale-international and Self-efficacy questionnaire were .81, .84 and .87 respectively. The data were analyzed using mean, percentage, standard deviation, and t-test. The significant difference was set at the .05 level. The research results were summarized as follows participants in experiment group after participating in self-efficacy promoting program had statistically significant lower fear of fall than before participating the program. And participants in experiment groups who participated in self-efficacy promoting program had statistically significant lower fear of fall than those who received conventional care.